2016
DOI: 10.12657/denbio.075.005
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of identification of negative extreme climatic events using Pinus sylvestris tree-rings in Transdanubia, Hungary

Abstract: Negative climatic extremes occur more frequently in the last decades. Since the Carpathian Basin is highly concerned in their impacts it is important to investigate prior events and estimate the response of the environment to them to get useful information for the future. In our work we selected a stand which is seriously affected by unfavorable summer conditions to examine what kind of fingerprint the negative extreme events have left. We investigated narrow rings and intra-annual density fluctuation to descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
(42 reference statements)
2
4
0
1
Order By: Relevance
“…It is interesting that we also found differences in the indicators related to winter and early spring temperatures (Table 1). Our findings agree with previous studies [5][6][7]41] that these factors have the most influence on tree-ring width formation of Scots pine. At the Polish site, the values of minimum temperature in the coldest month and mean temperature in the coldest quarter are lower than in Hungary (Table 1).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…It is interesting that we also found differences in the indicators related to winter and early spring temperatures (Table 1). Our findings agree with previous studies [5][6][7]41] that these factors have the most influence on tree-ring width formation of Scots pine. At the Polish site, the values of minimum temperature in the coldest month and mean temperature in the coldest quarter are lower than in Hungary (Table 1).…”
Section: Discussionsupporting
confidence: 94%
“…Research conducted on the Iberian Peninsula and in Mongolia show that rainfall deficiency in summer can be the most limiting factor for species establishment in southernmost localities, with low summer rainfall directly leading to high mortality of seedlings [34][35][36]. Water deficiency in the warmest quarter is also important as a limiting factor for radial growth of this species [7,8,37,38]. This might be the most important reason behind the absence of native populations of Scots pine in Hungary.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Temperature or precipitation played little or no role in the growth of Scots pine at high elevation; the only factor affecting growth was drought , which is an indication of potential limitation posed by climate if climate changes tend towards decreasing precipitation. Our research is in accordance with the findings of the other authors who found that the growth of Scots pine in the studied region mainly depends on the amount of available precipitation (Misi & Náfrádi, 2016) or severity of drought (Misi & Ná-frádi, 2017) and less on temperature (Sidor & Popa, 2015). Some authors found an indirect connection between climate and growth of Scots pine -Poljanšek et al (2015) found a close connection between a hot and dry summer and the number of needles of the terminal bud, while Panayotov et al (2012) found a connection between drought and partial or complete absence of latewood if the summer in the year of ring formation was dry and warm.…”
Section: Discussion Correlation Between Growth and Spisupporting
confidence: 93%
“…Az extrém események jelentős mértékben befolyásolják az adott évben keletkező évgyűrű jellemzőit, ezzel szignifikáns hatást gyakorolva az évgyűrűmintázatra. A szélsőség jellegétől függően kialakulhatnak világos évgyűrűk (Liang-Eckstein 2006), fagyott évgyűrűk (Hantemirov et al 2004;Kern-Popa 2008;Bräuning et al 2016), éven belüli sejtsűrűség ingadozások (de Luis et al 2011;De Micco et al 2013 Misi-Náfrádi 2016a), szokatlanul vékony évgyűrűk (Panayotov et al 2013;Misi-Náfrádi 2016a), de bizonyos esetekben lokálisan, vagy akár a törzs teljes keresztmetszetéből hiányzó évgyűrűk is. Ezen felsorolásból kiemelhető az éven belüli sejtsűrűség ingadozás, melyet korábban álévgyűrűként is aposztrofáltak, valamint a szokatlanul vékony évgyűrűk, ugyanis mindkét évgyűrűkarakter-módosulat jól azonosítható már makroszkóposan is, ezáltal marker jellegük kihangsúlyozódik, mely a keresztdatálás során fontos szempont lehet, továbbá az esetek többségében mindkettő markáns külső stresszhez köthető.…”
Section: Természetestől Eltérő éVgyűrűkarakterekunclassified